Nieruchomości jako lokaty przedsiębiorstw ubezpieczeniowych - Bożek-Węglarz, Sylwia (Properties as Investments of Insurance Companies, 2007)
The paper presents properties as insurers' investments. Real estate in insurance is a very special kind of investments, because it can be viewed as investment asset as well as property asset class. The analysis of the performance of investments in land and buildings in life and non-life insurance was based on profitability ratio of investments in land and buildings and profitability ratio of investments in land and buildings in portfolio. Ratios insurers' investments in property were accounted between 2000 and 2005. In general, in Poland, like in Europe, insurance companies invested in land and buildings in higher level in non-life insurance than life insurance. In 2003 in total insurance companies were in the process of changing their property investment policy, because insurers' purchases of properties generated losses, although losses decreased. At the end of 2002 profitability ratio of investments in land and buildings was calculated at only to 2.06% in life insurance, and it was the beginning of a decreasing trend. Non-life insurers registered decrease profitability properties also.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 37-45